Applicable Law Concerning Obligations Arising from the Infringements of Personal Data Laws Due to the Use of Artificial Intelligence Systems - Więckowski, Zbigniew; Świerczyński, Marek (Review of European and Comparative Law, 2023)
An issue that is characteristic of AI is data processing on a massive scale (giga data, Big Data). This issue is also important because of the proposition to require manufacturers to equip AI systems with a means to record information about the operation of the technology, in particular the type and magnitude of the risk posed by the technology and any negative effects that logging may have on the rights of others. Data gathering must be carried out in accordance with the applicable laws, particularly data protection laws and trade secret protection laws. Therefore, it is necessary to determine the applicable law in line with existing conflict-of-law regulations.